Health Adaptation Behavior of Farmers and Fishermen in Areas Exposed to Climate Change - Riviwanto, Muchsin; Barlian, Eri; Dwiyanti, Defriani (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Climate change is a definite, indisputable, clear, firm, and imminent reality, and has the potential to become a serious threat and challenge for the agriculture and fisheries sector. Climate change not only has an impact on the economy but also the health of farmers and fishermen. Farmers and fishermen must have health adaptation behavior to anticipate the adverse effects of climate change. This study aims to look at the individual's adaptive behavior and the factors that influence it. This study uses a cross sectional design on the heads of families of farmers and fishermen affected by climate change in the Province of West Sumatra, Indonesia. The number of samples as many as 150 samples were taken by probability proportional to size (PPS). Collecting data using primary data with interviews method. Data processed by computer and multivariate analysis with logistic regression testThe results of this study found the influence of husband's education, family income, self-efficacy, self-awareness, attitudes, perceptions, life skills, health care support, access to information about climate change together on health adaptation behavior. The most important determinants of health adaptation behavior are husband's education and self-awareness. There is a need for non-formal education in the form of socialization and training on adaptation of public health in the face of climate change. The government must integrate health and climate programs, climate socialization for health workers and provide compensation for people exposed to climate change.